Long-term follow-up of HIV-1-infected adults who received the F4/AS01B HIV-1 vaccine candidate in two randomised controlled trials. Issue 19 (3rd May 2018) - Harrer, Thomas; Dinges, Warren; Roman, François; ,
Highlights: F4/AS01B is a human immunodeficiency virus 1 (HIV-1) investigational vaccine. After ≥2 years of follow-up, F4/AS01B was well-tolerated in HIV-1-infected adults. A previous trial showed no clinical benefit of F4/AS01B in HIV-1-infected patients. The conclusion of the previous trial was unchanged after this long-term follow-up. Polyfunctional CD4 + T-cells persisted for ≥2 years after administration of F4/AS01B . Abstract: This Phase I/II, open, long-term follow-up study was conducted in antiretroviral therapy (ART)-naïve (N = 212) and ART-treated (N = 19) human immunodeficiency virus 1 (HIV-1)-infected adults, who received an HIV-1 investigational vaccine (F4/AS01B ) or placebo in two previous studies (NCT00814762 and NCT01218113). After a minimum of two years and a maximum of four years of follow-up post-vaccination per patient, no significant differences were observed between F4/AS01B and placebo groups in terms of viral load, CD4 + T-cell count and incidence of specific clinical events. Vaccine-induced polyfunctional CD4 + T-cells persisted up to study end and no relevant vaccine-related safety events were reported in F4/AS01B groups. This study has been registered atClinicalTrials.gov (NCT01092611).